Pengaruh Good Corporate Governance (GCG) dan Coporate Social Responsbility (CSR) Terhadap Nilai Perusahaan - Purwanto - Purwanto (Universitas Veteran Bangun Nusantara, 2021)
This pandemic seems to remind the importance of business continuity, that companies must pay attention to all internal and external stakeholders in order to increase company value. Good corporate governance or GCG is still one of the weaknesses that most companies in Indonesia have. The correct application of GCG can make a company bigger and more reliable. The purpose of this study is to determine the effect of projected GCG in institutional ownership, managerial ownership, audit committee and the Board of Commissioners and CSR on firm value. The sample in this study was 120 samples of data from manufacturing companies in the consumer goods industry sector. The results showed that the managerial ownership and CSR variables had a significant positive effect on firm value. The audit committee variable has a significant negative effect on firm value. and the variable of institutional ownership and the board of commissioners has no effect on firm value. and all independent variables together have a significant effect on firm value. Based on the results and analysis that has been carried out by researchers, hopefully this research can be useful for companies in increasing the value of the company by increasing the implementation of GCG and CSR disclosure and for investors to be taken into consideration in choosing issuers to invest.